Optimizing The Marketing Activities of Koperasi Jasa Pegawai Republik Indonesia (Kjpri) Of Universitas Brawijaya Through The Adoption Of Digital Technology - Rusydi, M. Khoiru; Handaru, Wuri Cahya; Riza, Muhammad Faisal; Umam, Khoirul; Kusumadewi, Areta Widya; Fitriana, Defi; Bilqisa, Yayang; Fauzia, Viramashita Ellena; Maesa, Sulton; Larasati, Wahyu Kartika; Jawo, Muhammed (The International Journal of Accounting and Business Society, 2023)
Purpose — The objective of this research is to optimize the marketing activities of Universitas Brawijaya’s Koperasi Jasa Pegawai Republik Indonesia (KJPRI UB) by utilizing digital technology through (1) identification of main problems using SWOT analysis on their website to identify the most suitable digital marketing strategy to be applied in the cooperative, (2) system enhancement and menu addition in their website, and (3) gradual socialization and assistance to ensure their business development. Design/methodology/approach — This qualitative case study uses the interview approach, so the results are analytical and descriptive in nature. The population of this research is all KJPRI throughout Indonesia, and the sample is KJPRI UB, which is located in Malang, East Java, Indonesia. Findings — This study finds that KJPRI UB has no features that provide convenience for their customers. Furthermore, changes from KPRI UB to KJPRI UB have required the cooperative to pay more attention to brand awareness through digital marketing. Practical implications—The results of this research can optimize the role of digital marketing in KJPRI UB, which also applies to other KJPRIs in Indonesia. Originality/value —This article presents digital marketing issues in KJPRI UB so that it can provide an example of digital marketing optimization for other KJPRI. Paper type — Case study